Effects of a pre‐existing food allergy on the oral introduction of food proteins: findings from a murine model. Issue 1 (28th November 2014) - Kulis, M.; Burks, A. W.
Abstract Cashew‐allergic mice develop elevated walnut‐specific IgE upon oral feeding of walnut proteins. Ingestion of tree nuts in the presence of a known nut allergy could lead to additional sensitizations and anaphylaxis following subsequent exposure.